Fertility-Sparing Surgery Using Knitted TiNi Mesh Implants and Sentinel Lymph Nodes: A 10-Year Experience. Issue 10 (17th September 2021) - Chernyshova, Alena; Kolomiets, Larisa; Chekalkin, Timofey; Chernov, Vladimir; Sinilkin, Ivan; Gunther, Victor; Marchenko, Ekaterina; Baigonakova, Gulsharat; Kang, Ji Hoon
Abstract: Objectives: The aim of this cohort study is to improve the procedure of fertility-sparing surgery and to assess oncological and reproductive follow-up outcomes after radical trachelectomy (RT) for cervical cancer (T1a2-1b Nx M0 ). Methods: We have suggested the method combining sentinel lymph nodes (SLNs) and cervicoisthmic cerclage using a superelastic knitted TiNi mesh (KTNM) implant to facilitate the primary biomechanical/retention function of the uterus. Sixty-eight consented patients, who underwent fertility-sparing surgery using both transabdominal and laparoscopic route from 2009 through 2019, were recruited in the study and prospectively followed for a mean of 69 months. Results: There were no intraoperative or postoperative complications. No cervical stenoses or mesh failures were noted in all cases. The 5‐year overall and recurrence‐free survival rates were 100% and 97%, respectively. Two patients indicated recurrence, it occurred in 3 and 36 months. There were 19 (28%) spontaneous pregnancies, 6 resulted in full-term delivery, whereas 2 and 11 ended in miscarriage and early abortion, respectively. Conclusions: This sparing-surgery technique is turned out to be feasible and efficient as allows to achieve well oncologic and fertility outcomes, mimicking the effect of the cervix. It complements existing surgical approaches and may provide further insight into how to overcome challenges even in aggravated cases or previously failed procedures.